2016
DOI: 10.1111/jfpp.12708
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Statistical Approach Towards an Optimized Production of Bacteriocin byLactobacillus pentosusTSHS

Abstract: Bacteriocins, antimicrobial compounds, display applications from food preservation to medicine. The aim of this study was the statistical optimization of a bacteriocin substance production from traditional cheese bacterium taxonomically affiliated as Lactobacillus pentosus TSHS. The effects of variables were first investigated using the Placket–Burman design. Central composite design was then used to compute incubation time and NaCl concentration optimum. Response surface methodology (RSM) revealed that maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…NaCl concentration and greenhouse time are effective in the optimal production of pentocin bacteriocin. The two mentioned factors among other factors (amount of tween, amount of peptone, amount of yeast extract, size of inoculum) were selected as the most effective factors in the production of pentocin using the statistical program of the response surface method (Motahari et al, 2016;Mirdamadi et al, 2017).…”
Section: Antimicrobial Peptides Antimicrobial Peptidesmentioning
confidence: 99%
“…NaCl concentration and greenhouse time are effective in the optimal production of pentocin bacteriocin. The two mentioned factors among other factors (amount of tween, amount of peptone, amount of yeast extract, size of inoculum) were selected as the most effective factors in the production of pentocin using the statistical program of the response surface method (Motahari et al, 2016;Mirdamadi et al, 2017).…”
Section: Antimicrobial Peptides Antimicrobial Peptidesmentioning
confidence: 99%
“…Pentocin 31-1 was identified as anti-Listeria lacidophilin produced by L. pentosus 31-1 (Liu et al, 2008). Motahari et al (2016) optimized the fermentation conditions of lacidophilin by L. pentosus and revealed that low concentration of sodium chloride promoted the production of lacidophilin. The study by Hurtado et al (2011) indicated that the appropriate concentration of sodium chloride could improve the bacteriostatic activity of L. pentosus B96 lacidophilin, compared with non-saline control and highconcentration sodium chloride group.…”
Section: Introductionmentioning
confidence: 99%